2004
DOI: 10.1083/jcb.200311031
|View full text |Cite
|
Sign up to set email alerts
|

DaPKC-dependent phosphorylation of Crumbs is required for epithelial cell polarity in Drosophila

Abstract: Both in Drosophila and vertebrate epithelial cells, the establishment of apicobasal polarity requires the apically localized, membrane-associated Par-3–Par-6–aPKC protein complex. In Drosophila, this complex colocalizes with the Crumbs–Stardust (Sdt)–Pals1-associated TJ protein (Patj) complex. Genetic and molecular analyses suggest a functional relationship between them. We show, by overexpression of a kinase-dead Drosophila atypical PKC (DaPKC), the requirement for the kinase activity of DaPKC to maintain the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
198
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(212 citation statements)
references
References 57 publications
12
198
2
Order By: Relevance
“…Other stocks used were: dlg-RNAi 4689 C2V (gift from B. Dickson, Dietzl et al 2007), validated for knockdown of Dlg and specificity , msn 06946 (msn-lacZ) (Mattila et al 2005); UAS-P35 (Hay et al 1994); UAS-bsk K53R (UAS-bsk DN ) (Weber et al 2000), UAS-aPKC DN (Betschinger et al 2003); UAS-aPKC CAAX-DN (Sotillos et al 2004); UASRas85D V12 (UAS-Ras ACT ) (Karim and Rubin 1998); UASRac1 N17 (UAS-Rac1 DN ) (Luo et al 1994); UAS-Rho1 RNAi #12734 [Vienna Drosophila Resource Center (VDRC), Dietzl et al 2007] and scrib 1 (D. Bilder).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other stocks used were: dlg-RNAi 4689 C2V (gift from B. Dickson, Dietzl et al 2007), validated for knockdown of Dlg and specificity , msn 06946 (msn-lacZ) (Mattila et al 2005); UAS-P35 (Hay et al 1994); UAS-bsk K53R (UAS-bsk DN ) (Weber et al 2000), UAS-aPKC DN (Betschinger et al 2003); UAS-aPKC CAAX-DN (Sotillos et al 2004); UASRas85D V12 (UAS-Ras ACT ) (Karim and Rubin 1998); UASRac1 N17 (UAS-Rac1 DN ) (Luo et al 1994); UAS-Rho1 RNAi #12734 [Vienna Drosophila Resource Center (VDRC), Dietzl et al 2007] and scrib 1 (D. Bilder).…”
Section: Methodsmentioning
confidence: 99%
“…We blocked aPKC activity by expression of a kinase-dead (dominant-negative) transgene (aPKC DN ) (Sotillos et al 2004), which in clones can suppress the defects of scrib or lgl mutants (Grzeschik et al 2007;Leong et al 2009). aPKC DN exhibited no effect upon the ey.Ras ACT phenotype (see Figure S5); however, it partially suppressed the cooperative effect of dlg RNAi with Ras ACT (Table 2 and see Figure S5), consistent with the antagonistic relationship between these proteins (as described previously).…”
Section: Uas-pbl-gfp#8mentioning
confidence: 99%
“…Strikingly, aPKC modulates p114RhoGEF activity by phosphorylating the adaptor protein Lulu2. aPKC and its modulator PAR-6, in turn, have been shown to associate with both Baz/PAR-3 and Crb (7,44,53). Therefore, association of PATJ with both complexes might serve as a scaffold to assemble different Myosin-modulating proteins in a defined compartment of the cell.…”
Section: Association With Both Crb-sdt and Baz-sdt Complexes Rather Tmentioning
confidence: 99%
“…The activity of these two complexes is counterbalanced by proteins such as Scribble-Lethal (2) giant larvaeDiscs large (Dlg), which localize to the basolateral domain. In the past, various studies have demonstrated that both apical complexes are rather dynamic and that their composition might be tissue-dependent and temporally and/or developmentally regulated (3)(4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…These include: Par-1/MARK, Par-3, GSK-3β, Lgl, and Crumbs (Suzuki et al, 2004;Izumi et al, 1998;Nagai-Tamai et al, 2002;Etienne-Manneville and Hall, 2003;Betschinger et al, 2003;Sotillos et al, 2004). In mammals, there are at least three Par-1/MARK (Microtubule Affinity-Regulating Kinase) homologs.…”
Section: Apkc Phosphorylation Substrates and Retinal Developmentmentioning
confidence: 99%